Life in Transit Theological and Ethical Contributions on Migration - Vorster, Jakobus (Reformed Theology in Africa Series, 2020)
Migration is an issue that is under discussion worldwide and affects South Africa, the United States of America and Germany in a distinctive way. This book reflects academically on this significant and topical subject of migration from the often neglected perspective of the fields of theology and Christian ethics. While the majority of contributions are from the South African context, there are also chapters reflecting on the topic from the other two aforementioned contexts. While numerous publications have recently appeared on the subject, reflection from theology and Christian ethics are often lacking. As such, this scholarly publication wants to add ethical value to the local and global conversations on the theme from a theological perspective. The book reflects on migration from the perspectives originated in the disciplines of biblical studies (the Hebrew Bible and the New Testament), systematic theology, ecumenical studies, Christian ethics, practical theology, and missiology. It presents new and innovative inquiries primarily from a qualitative methodological viewpoint. The book unveils new themes for deliberation and provides novel interpretations and insights into existing research.